In-service teacher training and professional context: how to respond to training needs? - Lopes, Carlos (2019)
Teachers' training has a long tradition in Portugal, since the creation of the Normal Schools until the publication of the Basic Education Law, which received a broad consensus in Portuguese society [1], namely in Article 35. In the context of in-service teacher training, some changes took place, being relevant what occurred with Decree-Law no. 127/2015 [2], for the present work, which establishes the Legal Regime of Schools Association Training Centers (SATC), within which the Training and Monitoring Section (TMS) was created. With the publication of [2], namely in articles 11 and 12, which defines the SATC direction and management structures, the TMS assumes an essential role in the coordination, pedagogical supervision and follow-up of the training plan and activities of the SATC. Reflecting this structure, the training plans of each of the associated schools, represented by the school grouping head for the training plan. According to Barroso and Canário [3], SATC plays a fundamental role in the contextualization of inservice teacher training, constituting a "school-centred" training mechanism and assuming as relevant the teaching establishment as a founder of needs and professional contexts as a privileged field of professional development. In this research, we aim to understand the role of TMS and its contributions to the development of educational projects of the school grouping and the monitoring of training plans. Thus, we opted by a quantitative approach, supported by a questionnaire survey (n = 170), structured in a set of open and closed questions in google forms, sent to the elements of the monitoring and evaluation section, for further statistical treatment with SPSS and content analysis.